A participação das fontes que representam o sistema jurídico na construção do caso Isabella: uma análise das revistas Época, Isto é e Veja - Cardoso, Jaqueline Da Silva Torres (Universidade do Vale do Rio dos Sinos, 2010)
The present research proposes a look over the complex relations between media and justice, marked, mainly by different temporalities. And it is in crimes with great repercussion with its vast media coverage that it is possible to have a better view of the hindrance which involves “media and justice”. For this reason, the focus of this research are the reports from the maganizes Época, Isto É and Veja which broach the “case Isabella” during the four following weeks of April 2008. This paper investigates how the discourse of such magazines was organized both to receive the juristic system participation through the sources which represent it, and to meet the deadlines of their journalistic productions, when they reported the case Isabella. Based on the methodological approach of the Content Analysis, we analyzed the frequency and the participation of the sources which represent the juristic field in the case Isabella. Moreover, we identified the circumstances in which the weeklies turned to other sources of information in order to deal with the conflict of temporality and the way these sources filled in information gaps produced by the silence of justice. Among our conclusions, it is noticeable that Época magazine searched for official sources that made it be neutral and careful, and also often suggest what should be done in the investigation process. Isto É turned to official sources to gather not only initial but also final information over the investigation process which could assure the guilt of the ones involved in the crime. Veja behaved as if it had all the information over the investigation process and did not have the need to search for them in the discourse of legal agents.
Keywords: Caso Isabella; Fontes jornalísticas; Justiça; Mídia; Revista; Tempo; Case Isabella; Journalistic sources; Justice; Media; Magazine; Time; ACCNPQ::Ciências Sociais Aplicadas::Comunicação